Impact of Compensation Factors on Teachers’ Job Satisfaction: An Econometric Focus - Kumar , Dhanonjoy (Global Disclosure of Economics and Business, 2016)
Compensation satisfaction represents an important construct to organizations and to the field of Human Resource Management because it serves as a critical mediator between an organization’s compensation policy and relevant behavioral and attitudinal outcomes (Blau, 1994; Lawler, 1981; Sturman & Short, 2000). Compensation plays a significant role in determining employees’ job satisfaction. According to Bozeman & Gaughan (2011), the perception of being paid what one is worth predicts job satisfaction. This study, therefore, seeks to establish the effects of compensation on job satisfaction among primary school teachers, secondary school teachers and college teachers in Bangladesh. The questionnaires prepared for this purpose are applied to 250 teachers who are currently working in various schools and colleges in Bangladesh. The collected data have been analyzed through several techniques by using SPSS 17.0 program. Analyses of the study reveal that a significant relation is observed between the compensation factors and the job satisfaction of the teachers. Overall, the teachers’ job satisfaction levels are not so elevated (mean value is 3.46 and a standard deviation is 0.982). Besides, the differences among the demographic variables (age, gender, monthly income level, job experience, and education) and the attitudes towards these factors and the levels of job satisfaction are also measured. This study provides significant information for educational institutions regarding compensation factors of job satisfaction.